لعبارات العلم بصفات ذاته من صفات أفعاله - الفزاري, عبد الله بن يزيد (الجمعية الليبية للدراسات الأمازيغية, 2025)
كتاب ««العبارات»» للإمام «عبد الله بن يزيد الفزاري» أحد النصوص التأسيسية في علم الكلام الإباضي، ويُمثّل حلقةً مهمة في تطوّر الفكر العقدي الإباضي في مرحلة النضج الميتافيزيقي التي تلت الجدل الكلامي المبكر حول صفات الله وأفعاله.والكتاب رسالة موجزة في بيان «الوحدانية والتنزيه لله تعالى والعلم بصفات ذاته وأفعاله»، وضعها الفزاري باختصار مقصود بقوله: «أردنا بكتابنا هذا جمل الأصول فيقاس عليها ما لم نذكر».
Keywords: Fazārī; ʿAbd Allāh ibn Yazīd al-; Foi – Traité – 8e siècle

Treatises on the Islamic firaq (Sects) and the Origin of Islamic kalām: Early Kufa-Baghdad Literature - Salimi, Abdulrahman al- (Studia Islamica, 2025)
Abstract This study examines two late 2nd/8th century books that have been edited and published recently: Abū Muḥammad ʿAbd Allāh b. Yazīd al-Fazārī (d. c.185/800)’s Kitāb al-Rudūd (The Book of Responses) and Ḍirār b. ʿAmr al-Ġaṭāfānī’s (d. c.200/810) Kitāb al-Taḥrīš (The Book of Provocation). Both texts shed light on the emergence of ʿilm al-kalām (scholastic theology) in early Islam and its relationship to books and treatises on the Islamic firaq (sects) – a relationship which until now has not been sufficiently examined. In comparing these two texts, we focus on the specific topics they share, the methodologies they use, and the technical terms they employ. We conclude that the emergence of ʿilm al-kalām, as well as the Islamic “contemplative disciplines” in general, occurred not primarily, as is often surmised, as a result of external Greek philosophical influence but rather as the result of a politico-theological debate that took place within Muslim communities. We also reconsider the nature of intellectual life during the early Abbasid period.
Keywords: Fazārī; ʿAbd Allāh ibn Yazīd al-; Foi – Traité – 8e siècle; Ġaṭāfānī; Ḍirār b. ʿAmr al-